A Different Story: Sex and Gender in Colette's Coming-Of-Age Novels - Holmes, Diana (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
Colette’s work charts the human life-course in the feminine, with a recurring focus on adolescence or the period of transition from childhood to adulthood. Whereas the classic patriarchal version of a girl’s accession to womanhood sees this in terms of her initiation into heterosexual love and desire by a more experienced male partner, Colette proposes a very different  model of female coming-of-age. In her work, girls achieve their own ‘sentimental education’ by recognising and asserting their own desires, which both encompass and transcend erotic desire. Analysis of a selection of her fiction demonstrates how her coming-of-age stories question the binary model of gender and sexuality that remained hegemonic in and beyond Colette’s own lifetime, and show how her characterisation of girls and boys on the cusp of adulthood refutes culturally embedded models of gendered difference, and invites her readers to question the dominant narrative of heterosexual coming-of-age.
Keywords: Colette; coming-of-age stories; sex; gender; sentimental education